Causes and consequences of Eastern Australia's 2019–20 season of mega‐fires: A broader perspective. (6th May 2020) - Adams, Mark A.; Shadmanroodposhti, Majid; Neumann, Mathias
Abstract : Climates—especially seasonal and long‐term droughts—and fuel loads combine to determine risks of wildfires across much of Australia. Here we illustrate how long‐term accumulations of fuel combined with a serious drought to drive the behaviour and extent of recent fires in South‐eastern Australia. This article is a commentary on Nolan et al. 26, 1039–1041 . See also the response to this letter by Bradstock et al. 26, e8–e9 .